When knowing is believing: A multi‐trait analysis of self‐reported TPCK. (24th March 2018) - Krauskopf, K.; Forssell, K.
Abstract: In an effort to understand teachers' technology use, recent scholarship has explored the idea of technological pedagogical content knowledge (TPCK or TPACK). Many studies have used self‐reports to measure this knowledge (SR TPCK). Several studies have examined the construct validity of these assessments by analysing the internal relationships of the knowledge domains, but little attention has been paid to how SR TPCK relates to external criteria. We tackled this question of discriminant validity by reanalysing 2 data sets. We used correlation and multiple regression analyses to explore whether conceptually related constructs explain any variance in participants' SR TPCK. In Study 1, we applied this strategy to German pre‐service teachers using technology use, attitudinal variables, and objective measures of teachers' knowledge of technology and pedagogy as external criteria. In Study 2, we examined measures of technology knowledge, experience, and pro‐technology beliefs for in‐service teachers in the United States. Across both studies, a sizeable amount of the variance in SR TPCK is explained by teachers' prior technology use and pro‐technology attitudes. In contrast, fact‐based tests of technology and pedagogy are distinct from SR TPCK. We discuss implications for these findings and argue that researchers should gather complementary measures in concert. Lay Description: What is already known about this topic: Technological pedagogical content knowledge (TPCK) is theorized to be an important aspect of teachers' use of technology. TPCK self‐reports seem intuitively helpful, and they are an easy way to quantify teachers' perceptions. The validity of TPCK self‐reports as knowledge measures is unproven. What this paper adds: Results of 2 studies show that TPCK self‐reports relate to beliefs and experience more than to knowledge of technology facts. Pre‐service teachers' self‐reports of their knowledge may be influenced by their enthusiasm for teaching with technology. In‐service teachers' beliefs about the value of technology appear to contribute meaningfully to TPCK self‐reports. Implications for practice and/or policy: Measures of experience and beliefs should be included when studying teachers' knowledge of technology. TPCK self‐reports may be used to complement factual knowledge measures as indicators of readiness to teach with technology.